Bubbles, crashes and information contagion in large-group asset market experiments - Cars H. Hommes; Anita Kopányi-Peuker; Joep Sonnemans (Tinbergen Institute, 2019)
We study the emergence of bubbles in a laboratory experiment with large groups of individuals. The realized price is the aggregation of the forecasts of a group of individuals, with positive expectations feedback through speculative demand. When prices deviate from fundamental value, a random selection of participants receives news about overvaluation. Our findings are: (i) large asset bubbles occur in large groups, (ii) information contagion through news affects behaviour and may break the coordination on a bubble, (iii) time varying heterogeneity provides an accurate explanation of bubble formation and crashes, and (iv) bubbles are strongly amplified by coordination on trend-extrapolation.
Keywords: C91; C92; D53; D83; D84; 330; Experimental finance; expectation formation; learning to forecast; financial bubbles